Relationship Between Human Capacity Building And Performance Of Micro And Small Enterprises (Mses) In Kisumu City - kithae, peter paul; Keino, Dinah C. (Archives of Business Research, 2016)
This paper focused on the relationship between human capacity building and performance of micro and small enterprises (mses) in kisumu city. Despite the central role of mses in employment, industrial transformation and poverty reduction, the competitiveness and growth prospects of mses fall below the levels required to meet challenges of increasing and changing basis for competition. Effective management of a company’s human resources is key to business survival in today’s world. Human capacity building can be particularly important for small firms. The need for human capacity building for SMEs in Kenya is of great significance if we are to increase the performance and growth of SMEs and at the same time reduce inefficiency, low productivity and the rate of failures of small firm. A descriptive research design was used to carry out the study. A sample of 320 mses was selected for study using quota and convenience sampling technique. Convenience sampling technique is used to simplify data collection procedures and to avoid the complications of simple random method since the researcher just picks on those who happen to be available and are willing, until the desired size is attained. Both qualitative and quantitative research designs which were descriptive in nature were used; as Gall and Borg noted, “Descriptive studies by nature emphasis interpretation.”